Knowledge sharing in a coopetition project team: An institutional logics perspective1. (25th April 2019) - d'Armagnac, Sophie; Geraudel, Mickaël; Salvetat, David
Abstract: Cooperation between firms is often addressed from the perspective of relationship organizing; however, we know little about people's working‐level engagement in collective action during interfirm projects. Focusing on cooperation between rival firms (coopetition), we explore how knowledge can be shared among participants. We offer insight into the management of interorganizational projects that are viewed as temporary organizations.